Red, rather than blue can promote fairness in decision-making - Ou Li; Yan Shi; Kuangran Li (Humanities & Social Sciences Communications)
Abstract The present study investigated the effect of colors red and blue on fair behavior in two economic games. Study 1 showed that the color red (vs. blue) could lead to a higher (vs. lower) offer in the ultimatum game, and that this effect was mediated by the perceived competitiveness. Study 2 introduced the impunity game and showed that the colors red and blue only affected offers in the ultimatum game, but not in the impunity game. These findings suggested that colors play a more influential role in strategic motives than in pure altruism in fair decision-making, and color-induced perceived competitiveness underlies this effect. This study presents the first empirical evidence of the relationship between colors and fairness in decision-making and offers a solution to nudge cooperative and fair behavior in allocation.